2021
DOI: 10.1002/ppap.202100083
|View full text |Cite
|
Sign up to set email alerts
|

Spark discharges in liquid heptane in contact with silver nitrate solution: Investigation of the synthesized particles

Abstract: In this study, spark discharges are generated in liquid heptane that is in contact with an immiscible solution of silver nitrate. The results demonstrate that the discharges produced at 22 kV voltage amplitude and 500 ns pulse width change the color of both liquids and lead to the formation of nanoparticles. Most particles collected from heptane are nanocomposites of Ag nanoparticles (<10 nm) in the hydrocarbon network. Meanwhile, the material collected from the silver nitrate solution is Ag nanoparticles (10–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…Finally, O is probably due to the oxidation of the nanoparticles. The oxidation may happen during synthesis (by the oxidative species during discharge such as OH and O) [ 39 ] or after being exposed to ambient air [ 42 ]. Figure 2 c shows the particle size distribution deduced by measuring the diameter of many particles imaged by TEM.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, O is probably due to the oxidation of the nanoparticles. The oxidation may happen during synthesis (by the oxidative species during discharge such as OH and O) [ 39 ] or after being exposed to ambient air [ 42 ]. Figure 2 c shows the particle size distribution deduced by measuring the diameter of many particles imaged by TEM.…”
Section: Resultsmentioning
confidence: 99%
“…After 30 min of discharge treatment at 10 Hz, both liquids change color, which indicates that they contain nanoparticles. In the previous study [ 39 ] where a solution of Ag-nitrate was used, Ag particles were synthesized in both liquids. Most particles collected from heptane were Ag nanoparticles (<10 nm) embedded in hydrocarbon network; meanwhile, the material collected from the silver nitrate solution was Ag nanoparticles (10–150 nm of diameter).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The discharge begins to burn in a mixture of water and oil vapors between the HV electrode and the water surface acting as a liquid electrode. This feature-a discharge in vapors of two liquids-is of potential use for plasmaassisted chemical reactions, for example, with liquid hydrocarbons (synthesis, conversion, etc) [52,53].…”
Section: The Gap 'Short-circuiting' Plasma Onsetmentioning
confidence: 99%
“…For instance, streamer discharges at the interface of water/heptane lead to carbonaceous nanomaterials [16], while H:SiOC nanomaterials are produced at the water/hexamethydisilazane interface [17]. Furthermore, when spark discharges are ignited in heptane in-contact with silver nitrate solution, Ag nanoparticles (5-10 nm) encapsulated in C-matrix are produced in heptane, and larger Ag particles (10-100 nm) are produced in solution [18]. Considering that the discharge changes the color of the solutions from colorless to milky, it may further be concluded that an emulsion is formed.…”
Section: Introductionmentioning
confidence: 99%